Functional state assessment on the dynamics of interparametric concatenations during exercise tests - Poderys, J.; Venskaityte, E.; Poderiene, K.; Buliuolis, A.; Vainoras, A. (Medicina, 2010)
The aim of this study was to complement an analytical approach by new methodology of data sequences analysis of muscular and cardiovascular indices during the assessments of functional state. The participants of the study were 14 elite Greco-roman wrestlers and they underwent two exercise tests 30 squats per 45 s while 12-lead ECG was recorded continuously and 30-s vertical jumps test while the height, contact and flight times of each jump recorded. The parametric interactions parameters and their sequences analysis based on a mathematical method founded upon a matrix theory were applied. The obtained results enabled to identify dynamical changes of the independence of parameters or an opposite phenomenon - interaction. The dynamics of ECG or performance parameters did not allowed to fi nd out the moments of critical changes during the exercising. The dynamics of concatenation between the time of push-off and the height of jumps while performing repeated jumps has a tendency to increase in the values of discriminant and the fl uctuations at some point of jumping task comes on. Analysis of concatenation between ECG or muscle performance parameters allows distinguishing the individual peculiarities which could be in value of discriminant, in time of exercising before the fl uctuations occurs, in character how the body behave as to compensate fatigue. It was concluded that assessment the dynamics of inter-parametric concatenation of physiological parameters based on the data sequences analysis provide a new approach in the field of functional state assessment allowing to reveal features of functional preparedness and fatigability during workloads.